REPRODUKSI IDENTITAS MAHASISWA TERNATE DI YOGYAKARTA - Sukran Iksan (UIN Fatmawati Sukarno Bengkulu, 2019)
Identity Reproductions of Ternate Student’s in Yogyakarta. This Study shows that identity is so important for an individual because it refers to boundaries that differs himself from others. In a group, identity will create a tradition or something that can be labeled as their ethnicity markers so they could differ themself from others. Symbols could be a typical identity characteristic to express something that important in the community as a domain to communicate in showing their existency or their identity. Moreover those symbols could connect them to another ethnics.